Uma sequência didática com embalagens de pipoca para o estudo de semelhanças - Ibrahim Filho, Georges (2016)
This paper presents an educational sequence for the Geometry classes, which explores the concept of similarity, focusing on the variation of the similarity ratio between linear measurement, areas measurements and volume of some polyhedrons. The problematic situation in this case involves a comparison between the prices of different popcorn packaging sizes in Bauru ́s movie theaters and its area.